OPTIMIZING INVESTMENT STRATEGIES THROUGH LOCAL WISDOM TO FOSTER COASTAL ECONOMIC DEVELOPMENT IN KLUNGKUNG REGENCY - Dewa Gde Yoga Permana; Gita Apsari Dewi; Ni Luh Sintya Wati (STIE PEMBANGUNAN TANJUNGPINANG, 2026)
The coastal areas of Klungkung Regency possess substantial economic potential, particularly in marine tourism, fisheries, and creative industries. However, these sectors face persistent challenges, including limited infrastructure, low community capacity, and unsustainable investment practices. This study explores how local wisdom–based investment strategies can be optimized to support coastal economic development. The core issue lies in the lack of integration between local cultural values and financial planning in tourism investment, resulting in underutilized economic opportunities. This research employs a descriptive qualitative approach, using secondary data from regional development reports, tourism statistics, and academic studies. Methods include content analysis and stakeholder mapping to uncover strategic alignments between investment practices and cultural preservation. The findings reveal that strategies based on ethnodevelopment, community-based tourism, and sustainable coastal planning significantly enhance local incomes, empower coastal MSMEs, and foster tourism resilience. Moreover, incorporating financial literacy and local participation strengthens long-term socio-cultural and economic sustainability. This study contributes to the design of culturally aligned investment policies and provides a replicable model for similar coastal regions.